2018
DOI: 10.1158/1078-0432.ccr-17-2260
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Open-Label Study to Identify a Dosing Regimen of the Pan-AKT Inhibitor AZD5363 for Evaluation in Solid Tumors and in PIK3CA-Mutated Breast and Gynecologic Cancers

Abstract: Results: Maximum tolerated doses were 320 mg, 480 mg and 640 mg for continuous (n=47), 4/7 (n=21) and 2/7 (n=22) schedules, respectively. Dose-limiting toxicities were rash and diarrhea for continuous, hyperglycemia for 2/7, and none for 4/7. Common adverse events were diarrhea (78%) and nausea (49%) and, for CTCAE grade ≥3 events, hyperglycemia (20%). The recommended Phase 2 dose (480 mg bid, 4/7 intermittent) was assessed in PIK3CA-mutant breast and gynecologic expansion cohorts: 46% and 56% of patients, res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 27 publications
8
96
0
1
Order By: Relevance
“…For FOXO3a, the large decrease in cytoplasmic staining and corresponding large increase in nuclear staining after 4.5 days' exposure seems likely to be a result of redistribution of FOXO3a within the cancer cell as a consequence of upstream changes in AKT signaling pathway activity. This is consistent with the data in paired biopsies from solid tumors in the capivasertib phase I study (13) and validates the preclinical observation of induction of nuclear accumulation of FOXO3a in BT474c breast cancer cells [human epidermal growth factor receptor 2 (HER2)-amplified PIK3CA-mutant] exposed to capivasertib (18). It has been reported that AKT pathway-driven phosphorylation of FOXO3a is arrested by AKT inhibition (18), permitting translocation of FOXO3a to the nucleus; in keeping with this, inverse associations were seen in our study between changes in nuclear FOXO3a and the pathway signaling markers pGSK3b and pS6.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…For FOXO3a, the large decrease in cytoplasmic staining and corresponding large increase in nuclear staining after 4.5 days' exposure seems likely to be a result of redistribution of FOXO3a within the cancer cell as a consequence of upstream changes in AKT signaling pathway activity. This is consistent with the data in paired biopsies from solid tumors in the capivasertib phase I study (13) and validates the preclinical observation of induction of nuclear accumulation of FOXO3a in BT474c breast cancer cells [human epidermal growth factor receptor 2 (HER2)-amplified PIK3CA-mutant] exposed to capivasertib (18). It has been reported that AKT pathway-driven phosphorylation of FOXO3a is arrested by AKT inhibition (18), permitting translocation of FOXO3a to the nucleus; in keeping with this, inverse associations were seen in our study between changes in nuclear FOXO3a and the pathway signaling markers pGSK3b and pS6.…”
Section: Discussionsupporting
confidence: 88%
“…The secondary biomarkers analyzed (pAKT, pS6, and FOXO3a) also showed significant changes in this study that are consistent with inhibition of the AKT pathway. The observed induction of pAKT is consistent with previous preclinical and clinical data; capivasertib increases phosphorylation of AKT itself, and it has been reported that this is due to the protein being held in a hyperphosphorylated but catalytically inactive form as a consequence of compound binding (8,13,16). Results were obtained from paired biopsies collected during two previous phase I studies (NCT01226316 and NCT01353781), albeit in metastatic solid malignancies (including those with PIK3CA mutation).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To block Akt activation, Akt inhibitors were applied, including MK2206 [30,31], AZD5363 [32,33] and LY294002 [34]. As shown, the Akt inhibitors completely blocked CNTF (25 ng/ mL, 15 min)-induced Akt activation (Fig.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 71%